Characterizing habitat suitability for a central‐place forager in a dynamic marine environment. Issue 5 (9th February 2018) - Briscoe, Dana K.; Fossette, Sabrina; Scales, Kylie L.; Hazen, Elliott L.; Bograd, Steven J.; Maxwell, Sara M.; McHuron, Elizabeth A.; Robinson, Patrick W.; Kuhn, Carey; Costa, Daniel P.; Crowder, Larry B.; Lewison, Rebecca L.
Abstract: Characterizing habitat suitability for a marine predator requires an understanding of the environmental heterogeneity and variability over the range in which a population moves during a particular life cycle. Female California sea lions ( Zalophus californianus ) are central‐place foragers and are particularly constrained while provisioning their young. During this time, habitat selection is a function of prey availability and proximity to the rookery, which has important implications for reproductive and population success. We explore how lactating females may select habitat and respond to environmental variability over broad spatial and temporal scales within the California Current System. We combine near‐real‐time remotely sensed satellite oceanography, animal tracking data ( n = 72) from November to February over multiple years (2003–2009) and Generalized Additive Mixed Models (GAMMs) to determine the probability of sea lion occurrence based on environmental covariates. Results indicate that sea lion presence is associated with cool( <14°C), productive waters, shallow depths, increased eddy activity, and positive sea‐level anomalies. Predictive habitat maps generated from these biophysical associations suggest winter foraging areas are spatially consistent in the nearshore and offshore environments, except during the 2004–2005 winter, which coincided with an El Niño event. Here, we show how a species distribution model can provide broadscale information on the distribution of female California sea lions during an important life history stage and its implications for population dynamics and spatial management. Abstract : We combine satellite telemetry, near‐real‐time remotely sensed oceanography, and statistical models to explore how lactating California sea lions ( Zalophus californianus, n = 72) may select habitat and respond to environmental variability over broad spatial and temporal scales within the California Current System.